Reinforcing Environmental Sustainability through Institutional Pressures, Green Supply Chain, and Customer Intention among Pakistani Manufacturing Firms A-Pilot Test - Muhammad Rahies Khan; Muhammad Mutasim Billah Tufail; Mubashir Ali Khan; Muhammad Shakeel (iRASD Journal of Management)
Achieving equilibrium between environmental sustainability and economic growth remains a challenge for business concerns across the globe. Developed countries have achieved this balance through re-designing and re-engineering their business operations to eco-friendly processes to some extent but developing countries are still in the transit phase. As this study incorporated an adapted questionnaire hence, this needs to examine the reliability and validity of the constructs. This study was conducted to measure the reliability and validity of the instrument designed to evaluate the role of institutional pressures in implementing green supply chain management practices and their impact on environmental sustainability through the moderating role of green marketing and mediating role of customer green purchase intention among manufacturing firms in Pakistan. The self-administered questionnaire was distributed among employees of manufacturing companies and customers of green products. A total of 200 questionnaires were distributed and 162 valid responses were received which were used for this pilot test. The initial content and face validity of the survey questionnaire were obtained from subject and field experts. However, the results of this pilot showed that all the constructs met the reliability and validity threshold and the instrument is valid to measure the theoretical model proposed for the study. The study suggested that easy access to credit should be given to augment economic growth.